Ecclesiology under pressure: the importance of theological solidarity language in 1 Thessalonians - Harriman, Ross (Perspectives in religious studies, 2017)
A neglected element in ecclesiological analysis of 1 Thessalonians studied in this paper is the crucial link between ecclesiology and its theological roots. Paul forges this link through “theological solidarity language.” Theological solidarity language is language that solidifies bonds within the group and with God by rooting the communal identity in common beliefs in and relationships with this God. Paul uses this language to reaffirm and reemphasize communal identity and solidarity against communal conflict and suffering. The particular shapes this language takes in 1 Thessalonians include insider language and theological and pneumatological incorporation into union with God